Lake operation optimization of nutrient exports: Application of phosphorus control in the largest subtropical lake in the United States. (February 2023) - Tarabih, Osama M.; Dang, Thanh Duc; Paudel, Rajendra; Arias, Mauricio E.
Abstract: This paper presents Lake Operation Optimization of Nutrient Exports (LOONE), a Python-based model with three coupled modules: 1) a water balance module to simulate hydrology and operations, 2) a nutrient module to simulate phosphorus dynamics in the water column, and 3) an optimization tool to design optimal reservoir releases. We applied the model to Lake Okeechobee (Florida, USA), a shallow subtropical lake receiving and exporting excessive amounts of nutrients, while providing water supply, recreation, and flood control. We evaluated LOONE under historical operation schedules for model verification, and then designed optimal releases that minimized phosphorus exports into the two main distributaries of Lake Okeechobee. We found that P loads could decrease by 12–33% under optimal operations. The software package could be used to evaluate management decisions to help control water quality issues such as high nutrient exports and harmful algal blooms in Lake Okeechobee and reservoirs worldwide. Highlights: We developed a model to manage operations of nutrient impaired reservoirs. The model includes dynamic phosphorus balance coupled with an optimization algorithm. The model was evaluated to minimize phosphorus release from Lake Okeechobee.